Trioecy in the Marine Mussel Semimytilus algosus (Mollusca, Bivalvia): Stable Sex Ratios Across 22 Degrees of a Latitudinal Gradient - Oyarzún, Pablo A.; Nuñez, José J.; Toro, Jorge E.; Gardner, Jonathan P. A. (Frontiers in Marine Science, 2020)
Trioecy, the co-occurrence of males, females and hermaphrodites in natural populations, is a relatively common sexual system in plants, but is rare and poorly understood in animals. Previously, the marine mussel, Semimytilus algosus, has been described as a simultaneous hermaphrodite and there are reports of unisex animals in the wild. Here, we confirm trioecy in this bivalve, the first report of trioecy in the phylum Mollusca. We examined the frequencies of females, males and hermaphrodites in seven natural populations along a latitudinal gradient of ∼2500 km and carried out a phylogenetic analysis with mussel species of the family Mytilidae with known sexual systems. Hermaphrodites (∼95.3%), females (∼3.6%), and males (∼1.1%) were found in all seven populations across the species’ range in Chile. The consistent sex ratios across all populations suggest that the sexual system is stable in space. Phylogenetic analysis (mtDNA) of members of the family Mytilidae indicates that this species alone has developed trioecy from dioecious ancestors. As unisex animals were the least common in the wild, it is likely that these animals, especially males, might be in the process of being lost in this species, and that trioecy might be an intermediate step towards gynodioecy or hermaphroditism. The reproductive characteristics of S. algosus make it an excellent model species for the study of the evolution of sexual systems in animals and also possibly the processes underlying sex determination in molluscs.